OPTIMALISASI STRATEGI PERTAHANAN ELEKTRONIKA TNI MELALUI TATA KELOLA OPERASI GABUNGAN NASIONAL - Juli Praptono Teguh Eko Wibowo; Mitro Prihartoro; Dudik Purwanto (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2025)
This study explores the implementation of electronic warfare (EW) strategies in joint operations of the Indonesian National Armed Forces (TNI) in the modern era. The primary focus of the research is to identify the challenges and strategies applied in electronic warfare to support TNI's military missions. Electronic warfare plays a crucial role in controlling the electromagnetic spectrum, protecting communication systems, and disrupting enemy communications. Although TNI has integrated electronic warfare into its operations, significant obstacles remain, such as technological limitations, insufficient personnel training, and system integration issues between units. This research employs a qualitative approach with data collection techniques through in-depth interviews and document analysis. The findings reveal that technological advancements, more comprehensive training programs, and improved interoperability between units are key to enhancing the effectiveness of TNI's electronic warfare strategies. The recommendations include technology modernization, personnel training development, and the implementation of better interoperability standards in TNI's joint operations.